Lomografi Sebagai Komoditas Dan Media Ekspresi Masyarakat Urban - Wahyudi, Johan Ies (Institut Seni Indoensia Surakarta, 2010)
Digital carema technology is growing rapidly at this very indulgent lovers of photography, the image recording media facilities are also equiooed with sophisticated large data storage capacity and with a slim shape, making analog cameras are being abandoned. Analog camera is considered impractical because of the media are still using celluloid film recorder with a limitied number of photos, and not to mention the cost and time wasted to process film and print. This condition contrasts with the results of digital camera images that can be dircttly transferes and enjoyed on a computer screen. So if the world of analogue photography has been forgotten? Through the media Lomografi, analog photography as finding a new passion.LOMO is a phenomenon that is present in the digital age. LOMO cameras are still using celluloid film as a media recorder. The uniqueness of the camera and the images produced by LOMO camera makes quite a lot of people start experimenting to try it, so Lomografi in its development could create their own communities. In this article the author describes aspects of existence Lomografi, which begins by looking at commodities as a form of community Lomografi urban youth as this part of the tool to actualize themselves in their group who later gave birth to the consumtion of lomo cameras that serves as a lifestyle and a medium of expression for urban society.Keywords : Lomografi, expression media, lifestyle